2019
DOI: 10.1111/bph.14852
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of microRNA‐494 inhibits the neurotoxic Th1 shift via regulating HDAC2‐STAT4 cascade in ischaemic stroke

Abstract: Background and Purpose T helper cell 1 (Th1)‐skewed neurotoxicity contributes to the poor outcome of stroke in rodents. Here, we have elucidated the mechanism of the Th1/Th2 shift in acute ischaemic stroke (AIS) patients at hyperacute phase and have looked for a miRNA‐based therapeutic target. Experimental Approach MiR‐494 levels in blood from AIS patients and controls were measured by real‐time PCR. C57BL/6J mice were subjected to transient middle cerebral artery occlusion, and cortical neurons were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…Importantly, in the case of the latter miRNA, protection against the development of the tumors comes at a cost of elevated susceptibility to neurotoxicity, after exposure to ischemia/ reperfusion for example. Notably, knockdown of hsa-miR-494-5p reverses the neurotoxic phenotype in multiple models (Song et al, 2017;Deng et al, 2019;Zhao et al, 2019a;Zhao et al, 2019b). Hsa-miR-494-5p-dependent antagonistic relationships between gliomagenesis and neurotoxicity are intriguing, as they support previously noted decrease in odds of the development of brain tumors in patients with schizophrenia (Grinshpoon et al, 2005;Levav et al, 2007;.…”
Section: Discussionsupporting
confidence: 57%
“…Importantly, in the case of the latter miRNA, protection against the development of the tumors comes at a cost of elevated susceptibility to neurotoxicity, after exposure to ischemia/ reperfusion for example. Notably, knockdown of hsa-miR-494-5p reverses the neurotoxic phenotype in multiple models (Song et al, 2017;Deng et al, 2019;Zhao et al, 2019a;Zhao et al, 2019b). Hsa-miR-494-5p-dependent antagonistic relationships between gliomagenesis and neurotoxicity are intriguing, as they support previously noted decrease in odds of the development of brain tumors in patients with schizophrenia (Grinshpoon et al, 2005;Levav et al, 2007;.…”
Section: Discussionsupporting
confidence: 57%
“…Given that our preceding bioinformatics analysis indicated that miR‐494 target genes are involved in the focal adhesion molecule pathway, 13 we investigated the expression of the classical adhesion molecules CD11b and MMP9 in the peripheral neutrophils of AIS patients and analyzed their relationship with the miR‐494 levels. Consistent with bioinformatics analysis, both CD11b and MMP9 were prominently increased in neutrophils of AIS patients and were negatively associated with miR‐494 expression in neutrophils (Figure 2A‐D; P < .05).…”
Section: Resultsmentioning
confidence: 99%
“…Venous blood samples from AIS patients and healthy controls were collected into K3EDTA tubes, and neutrophils were separated by a standard Ficoll‐Paque Plus gradient method as previously reported 13 . Then, neutrophils were suspended in 0.5 mL of TRIzol and frozen at −80°C prior to the test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations